Digital humanities project proposal: Clipping of online and printed journals on education and institutes of education, science, and technology - Raupp Coutinho, Kênia (Advanced Notes in Information Science, 2023)
Clipping of online and print journals about education and the Federal Institutes of Education, Science, and Technology is a project at the strategic and planning level of Digital Humanities (DH). This project will be presented as a proposal for the implementation of services in libraries at IFSC, as well as other digital tools to organize information about the services offered. However, details about execution and feasibility are not provided in this article. This project aims to introduce the clipping service at IFSC based on the monitoring and selecting news about the Federal Institutes of Education, Science, and Technology, as well as education in general, published in digital and printed journals. In the cases of printed journals, they will be digitalized for inclusion in the platform. One of the authors is a librarian at IFSC. Therefore, she elaborated this proposal based on a need identified at the institution, possibly resulting in benefits for the institution's internal and external community and society in the present and near future.